2012
DOI: 10.3727/152599512x13539583375171
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Segmented Spectator Markets of a Minor League Baseball (MiLB) Team

Abstract: This study aimed to examine different segments of spectators at minor league baseball games in motivation, external factors, and their consumption behaviors. Using spectator identification, a combined scale of fan identification and sport identification, spectators were grouped into four clusters using K-means cluster analysis. Multivariate analysis of variance and chi-square tests were conducted to determine group differences. The results showed significant mean differences in the dimensions of motivation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The Leximancer analysis found that their experiences were built on three significant themes, "game," "stadium," and "team." Moreover, most of concepts of these themes are mainly relevant to the core and peripheral elements of sport events (Byon et al, 2013;Kotler et al, 2014;Lee & Won, 2012;Mullin et al, 2014). First, the theme "game" pertains to the core elements of sport events, indicating the distinctive atmosphere of watching Korean professional baseball games.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Leximancer analysis found that their experiences were built on three significant themes, "game," "stadium," and "team." Moreover, most of concepts of these themes are mainly relevant to the core and peripheral elements of sport events (Byon et al, 2013;Kotler et al, 2014;Lee & Won, 2012;Mullin et al, 2014). First, the theme "game" pertains to the core elements of sport events, indicating the distinctive atmosphere of watching Korean professional baseball games.…”
Section: Discussionmentioning
confidence: 99%
“…The second theme "stadium" refers to the physical environment and several services in the stadium which are related to various peripheral elements of sport events (Byon et al, 2013;Kotler et al, 2014;Lee & Won, 2012;Mullin et al, 2014). For example, the concepts of stadium and seats represent the experience of physical surrounding and facility qualities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, Wakefield and Inman concluded that consumers are less price sensitive when consuming products with other people. Various studies have also consistently found that attending sporting events with family and friends have a significant influence on consumers' attendance decisions (Boyd & Krehbiel, 1999Lee & Won, 2012;McDonald & Rascher, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has indicated these peripheral factors (i.e., promotions) have gained more interest because they can be controlled by the sport marketer (Boyd & Krehbiel, 2003McDonald & Rascher, 2000), unlike the team's performance. The results of the sport marketing studies have shown marketing promotions are influential on a consumer's decision to attend a sporting event (Boyd & Krehbiel, 2003Fink et al, 2002;Gifis & Sommers, 2006;Lee & Won, 2012;McDonald & Rascher, 2000). In fact, previous research has shown that these promotional efforts are indeed effective at increasing attendance (19.6%), and the positive effects of marketing promotions are on the rise (Boyd & Krehbiel, 2003Gifis & Sommers, 2006;McDonald & Rascher, 2000).…”
Section: Introductionmentioning
confidence: 99%